Analisis Kebijakan Dividen melalui Indikator Sektor Perbankan di 5 Negara ASEAN - Meirawati, Eka; Hamzah, Ruth Samantha; Gozali, Efva Octavina Donata; Azzahra, Aisyah; Chulim, Felix Rafael (Jurnal Akuntansi, Keuangan, dan Manajemen, 2024)
Purpose: This study delves deeper into dividend policies through the lens of the banking sector in five ASEAN countries. Methodology/approach: The study spans a nine-year observation period from 2011 to 2019, encompassing a total sample of 46 banking firms. Using multiple linear regression analysis with the ordinary least squares (OLS) method, secondary data were collected annually from the financial and annual reports of banking firms listed on stock exchanges in Vietnam, Indonesia, the Philippines, Thailand, and Malaysia. Results/findings: The findings reveal that within the banking sector of these five ASEAN countries, the Gross Profit Margin (GPM) negatively and significantly impacts the Dividend Payout Ratio (DPR), while the Return on Assets (ROA), bank size, and Asset Turnover Ratio (ATR) positively and significantly influence the DPR. Conversely, the Loan-to-Deposit Ratio (LDR), Non-Performing Loans (NPL), and Total Profit Ratio (TPR) do not significantly affect DPR. These results underscore the importance of financial performance in shaping dividend policies within ASEAN financial markets. Limitations: The study focuses on five ASEAN countries and specific financial variables, which may not fully represent the banking sector dynamics of the entire region. Contribution: This study provides valuable insights into the banking sector in ASEAN countries by highlighting the link between financial performance and dividend policies